Congenitally Corrected Transposition Presenting in the First Year of Life: Survival and Fate of the Systemic Right Ventricle. Issue 1 (January 2019) - Smood, Benjamin; Kirklin, James K.; Pavnica, Jozef; Tresler, Margaret; Johnson, Walter H.; Cleveland, David C.; Mauchley, David C.; Dabal, Robert J.
Introduction: Knowledge gaps exist in the life expectancy and functional outcome of patients with congenitally corrected transposition (ccTGA) presenting early in life, which is relevant in the evaluation of early anatomic repair. Methods: In a single-center analysis, 91 patients with ccTGA were identified over 25 years, of which 31 presented with biventricular anatomy in the first year of life and formed the study cohort. End points for analysis included survival, moderate or worse tricuspid valve regurgitation, and systemic right ventricle (RV) dysfunction. Median follow-up was 4.9 years (range: 7 days to 20 years). Results: Among 31 patients presenting in the first year of life, 9 (29%) never received cardiac surgery, while 22 (71%) underwent 36 cardiac operations. Overall freedom from moderate or severe systemic RV dysfunction was 75% at 10 years. Overall survival was 82% at 10 years. Surgical mortality was 5.6% (2/36). Among survivors with a systemic RV, 23 (100%) of 23 were Ross or NYHA class I or II at last follow-up. Conclusions: Congenitally corrected transposition presenting in the first year of life and maintaining a systemic RV can expect (1) long-term survival of more than 80% at 10 years, (2) low expected surgical mortality (overall 6%), and (3) 75% late freedom from major RV dysfunction at 10 years. Pending multi-institutional analyses, this experience with a systemic RV in ccTGA provides an initial benchmark for comparison when considering early elective anatomic correction.